PRESERVATION OF THE HISTORICAL, ARCHITECTURAL, AND URBAN-PLANNING HERITAGE OF THE KITAB-SHAKHRISABZ REGION - Гильманова Нафиса Валиахметовна (Web of Journals Publishing, 2025)
The article examines issues related to the preservation of the historical, architectural, and urban-planning heritage of the Kitab-Shakhrisabz region. The processes of modern urbanization continue, while awareness of the high historical and cultural significance of Shakhrisabz is being maintained. Its unique architectural monuments, which took shape in the 15th century, form part of the world’s cultural heritage and require systematic and comprehensive study and preservation – both of the monuments themselves and of their urban environment.
Keywords: Shakhrisabz, Kitab, urban planning, Kitab-Shakhrisabz region, preservation of architectural heritage, urbanization.